An experimental examination of the house money effect in a multi-period setting - Lucy F. Ackert; Narat Charupat; Bryan K. Church; James Tompkins; Richard Deaves (Federal Reserve Bank of Atlanta, 2003)
There is evidence that risk-taking behavior is influenced by prior monetary gains and losses. When endowed with house money, people become more risk taking. This paper is the first to report a house money effect in a dynamic, financial setting. Using an experimental method, the authors compare market outcomes across sessions that differ in the level of cash endowment (low and high). Their experimental results provide strong support for a house money effect. Traders' bids, price predictions, and market prices are influenced by the amount of money that is provided prior to trading. However, dynamic behavior is difficult to interpret due to conflicting influences.
Keywords: 330; Financial markets; Investments; Risk